Highly mixed impacts of near‐future climate change on stock productivity proxies in the North East Atlantic. Issue 3 (14th December 2021) - Kjesbu, Olav Sigurd; Sundby, Svein; Sandø, Anne Britt; Alix, Maud; Hjøllo, Solfrid Sætre; Tiedemann, Maik; Skern‐Mauritzen, Mette; Junge, Claudia; Fossheim, Maria; Thorsen Broms, Cecilie; Søvik, Guldborg; Zimmermann, Fabian; et al.
Abstract: Impacts of climate change on ocean productivity sustaining world fisheries are predominantly negative but vary greatly among regions. We assessed how 39 fisheries resources—ranging from data‐poor to data‐rich stocks—in the North East Atlantic are most likely affected under the intermediate climate emission scenario RCP4.5 towards 2050. This region is one of the most productive waters in the world but subjected to pronounced climate change, especially in the northernmost part. In this climate impact assessment, we applied a hybrid solution combining expert opinions (scorings)—supported by an extensive literature review—with mechanistic approaches, considering stocks in three different large marine ecosystems, the North, Norwegian and Barents Seas. This approach enabled calculation of the directional effect as a function of climate exposure and sensitivity attributes (life‐history schedules), focusing on local stocks (conspecifics) across latitudes rather than the species in general. The resulting synopsis (50–82°N) contributes substantially to global assessments of major fisheries (FAO, The State of World Fisheries and Aquaculture, 2020), complementing related studies off northeast United States (35–45°N) (Hare et al., PLoS One, 2016, 11, e0146756) and Portugal (37–42°N) (Bueno‐Pardo et al., Scientific Reports, 2021, 11, 2958). Contrary to prevailing fisheries forecasts elsewhere, we found that most assessed stocks respond positively. However, the underlying, extensive environmental clines implied that North East Atlantic stocks will develop entirely different depending upon the encountered stressors: cold‐temperate stocks at the southern and Arctic stocks at the northern fringes appeared severely negatively impacted, whereas warm‐temperate stocks expanding from south were found to do well along with cold‐temperate stocks currently inhabiting below‐optimal temperatures in the northern subregion.